Penetapan Wasiat Wajibah untuk Saudara Non Muslim dalam Kajian Maslahat - Setyaningrum, Fatimah khosiyyah setyaningrum; Waty, Wan Hamidah Febry; Salsabilah, Deswita Putri; Habil, Habil; Ardita, Tiara; Fauzan, Ahmad (CV. Doki Course and Training, 2025)
This study examines the Banten High Religious Court Decision Number 0092/Pdt.G/2017/PTA.Btn. with the concept of maslahat which highlights interfaith inheritance disputes between Muslim and non-Muslim heirs. The focus of the study is the construction of judges' considerations in the distribution of inheritance assets, including the proportion of distribution, the basis of ijtihad used, and the legal implications for the protection of heirs' rights. This study is a qualitative study with a normative legal approach, which emphasizes the analysis of laws and regulations, court decisions, and related legal documents. The results show that judges continue to prioritize the rights of Muslim heirs according to Article 171 letter (c) of the Compilation of Islamic Law, while applying mandatory bequest for non-Muslim siblings to maintain a balance of justice and family harmony. The use of legal analogy (qiyas) in determining the rights of non-Muslims reflects the flexibility of Islamic law in adapting formal rules to real social conditions. In conclusion, this decision serves as an example of adaptive legal practice that combines compliance with formal law with the achievement of social welfare, justice, and stability, while also emphasizing the relevance of the concept of maslahah in resolving interfaith inheritance disputes.